Highly effective transformation of methyl phenyl carbonate to diphenyl carbonate with recyclable Pb nanocatalyst. Issue 35 (1st July 2019) - Wang, Songlin; Niu, Hongying; Wang, Jianji; Chen, Tong; Wang, Gongying; Zhang, Jiamin
Abstract : PbO/MgO and PbO/ZrO2 with a high number of Lewis acid sites act as efficient catalysts for MPC disproportionation. Abstract : Diphenyl carbonate (DPC) is a type of versatile industrial chemical, and the disproportionation of methyl phenyl carbonate (MPC) is a key step to produce DPC. However, the design and formulation of a catalyst for the efficient synthesis of DPC is a major challenge due to its small equilibrium constant. The support material is a critical factor influencing the performance of Pb nanocatalysts. Thus, a series of Pb-based catalysts over MgO, ZrO2, SiO2, TiO2 and Al2 O3 were prepared to investigate the effect of the support materials on the physicochemical properties and catalytic performances for the conversion of MPC to effectively synthesize DPC. The catalysts were well characterized by XRD, BET, TEM, XPS, ICP-OES, H2 -TPR, Py-IR and NH3 -TPD. The results showed that the nature of the support obviously affected the structural properties and catalytic performances, and Pb was dispersed better on SiO2, TiO2, ZrO2 and MgO than on Al2 O3, and showed stronger metal-support interaction over MgO and ZrO2 . The activity results revealed that PbO/MgO and PbO/ZrO2 exhibited higher catalytic activities because they contained higher Pb dispersion and more Lewis acid sites, and the catalytic activities followed the order PbO/MgO > PbO/ZrO2 > PbO/SiO2 > PbO/Al2 O3 > PbO/TiO2 . On the contrary, PbO/MgO and PbO/ZrO2 exhibited better reusability due to strong interaction between the highly dispersed Pb and the supports, and the activity decrease in the case of PbO/SiO2, PbO/Al2 O3 and PbO/TiO2 mainly resulted from the Pb leaching loss. This work would contribute to exploiting novel catalytic materials in a wide range of applications for the efficient synthesis of organic carbonates.